IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM MENINGKATKAN MUTU LULUSAN DI SMA MUHAMMADIYAH 2 BUKIT KECIL PALEMBANG - Saputra, Handi (UNISAN JURNAL, 2023)
Improving the quality of graduates is one of the main objectives of an educational institution, namely by implementing School-Based Management (SBM). This research aims to determine the implementation of School-Based Management (SBM) in improving the quality of graduates at SMA Muhammadiyah 2 Bukit Kecil Palembang. This research method uses qualitative research with a descriptive approach. And the data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results showed that the implementation of School-Based Management (SBM) implemented at SMA Muhammadiyah 2 Bukit Kecil Palembang was quite good. As for the quality of graduates, it has not been able to achieve satisfactory results, it can be seen that the ability of students, especially in the value of Religious Education (theory) which has decreased by -2.46%. This is due to the limited infrastructure to support the learning process. The solution is the existence of good school leadership and management, the ability of parents to pay for education, as well as the level of passion and self-involvement in encouraging children to continue learning and the existence of government support.